Redesign Logo sebagai Corporate Identity pada Tureno di Kota Malang - Muhammad Zulfan Abiyyi Anwar; Joni Dwi Pribadi; Heru Utomo (INDO PUBLISHING, 2026)
Tureno is a business speacializing in the laundry parfume sector, and is committed to providing high-quality products with long-lasting fragrance. However, the business still uses a template-based logo that does not hold any intellectual property rights (IPR), making it less effective in building a strong visual identity and posing potential legal risks. Related to this, the purpose of this research was to redesign the logo as a corporate identity that is original, effective, and able to represent the character of Tureno.This study used the Action Research method, which includes the stages of planning, action, observation, and reflection. The logo was designed using CorelDRAW 2020 and involved 15 respondents, consisting of 1 business owner, 2 design experts, 2 marketing experts, and 10 consumers or potential consumers. The data collection techniques included observation, interviews, documentation, and questionnaires. The effectiveness of the logo design was measured based on Carter’s theory in Sitorus et al., (2022), which includes six key indicators: Original & Distinctive, Legible, Simple, Memorable, EasilyAssociated with the Company, and Easily Adaptable for All Graphic Media. The results showed that the redesigned logo fulfilled all the indicators and was considered effective and suitable to be used as Tureno’s corporate identity. The respondents agreed that the new logo successfully represents the character of the business, is easy to remember, and can be applied across various media. Thus, the logo can serve as the official identity that supports Tureno's brand image and enhances its competitiveness in the laundry perfume industry.